A Fast Implicit Finite Difference Method for Fractional Advection-Dispersion Equations with Fractional Derivative Boundary Conditions. (24th September 2017) - Liu, Taohua; Hou, Muzhou
Abstract : Fractional advection-dispersion equations, as generalizations of classical integer-order advection-dispersion equations, are used to model the transport of passive tracers carried by fluid flow in a porous medium. In this paper, we develop an implicit finite difference method for fractional advection-dispersion equations with fractional derivative boundary conditions. First-order consistency, solvability, unconditional stability, and first-order convergence of the method are proven. Then, we present a fast iterative method for the implicit finite difference scheme, which only requires storage of O ( K ) and computational cost of O ( K log ⁡ K ) . Traditionally, the Gaussian elimination method requires storage of O ( K 2 ) and computational cost of O ( K 3 ) . Finally, the accuracy and efficiency of the method are checked with a numerical example.